Mind vs matter: Economic and psychologic determinants of take-up rates of social benefits in the UK - Melchior Vella; Matteo Richiardi (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2024)
This paper investigates the behavioural dynamics of the take-up of social benefits in the UK. Utilising data from the first nine waves (2010-2019) of the UK Household Longitudinal Study (UKHLS) and eligibility simulations based on the UKMOD tax-benefit calculator (UKHLS-UKMOD), the study finds that there is a significant state dependence effect once initial conditions and unobserved heterogeneity are considered. While economic factors are found to play an important role in explaining the take-up of social benefits, personality traits and cognitive skills do not exhibit a strong and direct influence on the take-up of social benefits. The study concludes by discussing policy implications.
Keywords: 330; Microsimulation; Life Course Analysis; Surveys; Psychology; Welfare Benefits; Economics; Area Effects; Geography